English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

-5x + 3y= 6
x-y=4

If you would like your answer to be picked as the best answer, please do the following:

Please include all work

Please give steps on how you've completed it

Please give tips

Please give final answer in coordinates

2007-02-13 02:56:19 · 3 answers · asked by John S 1 in Science & Mathematics Mathematics

3 answers

-5x + 3y = 6 ---(1)
x - y = 4----(2)
3x(2)
3x - 3y = 12 ---(3)
(1) + (3)
-2x = 18
x = -9
subsititute into (2)
-9 - y = 4
y = -13
(-9,-13)

2007-02-13 03:34:06 · answer #1 · answered by seah 7 · 1 0

first pick out a variable you want to eliminate. let's go with y.

so multiply the bottom equation by 3 that way, the y's cancel out.

so...
-5x+3y=6
3(x-y)=3(4)

-5x+3y=6
3x-3y=12

so when you add the bottom from the top, you get...

-2x=18
x=-9

plug x back in.

-9-y=4
-y=5
y=-5

(-9,-5)

2007-02-13 03:01:45 · answer #2 · answered by eriq p 4 · 0 0

-5x+3y=6
3x-3y=12
adding
-2x=18
x=-9
sub in -5x+3y=6
45+3y=6
3y=39
y=13
soln.set(-9,13)

2007-02-13 03:06:26 · answer #3 · answered by raj 7 · 0 0

fedest.com, questions and answers